(untitled) (University of Khartoum Engineering Journal, 2022)
Khartoum airport plays a vital role in air traffic and national economy. The airport has experienced poor performance and lack of services. Serious congestion, delay and cancellation problems in flights becoming a daily habits. The study aims to evaluate the existing airport facilities and services and their ability to meet future demand. The literature concerning airport capacity and performance related issues were reviewed. The research depend on documents information, site inspection, and interviews for evaluation. The historical data of travelers at the Airport were analysed to estimate the forecasted demand. The study has identified challenges facing the increasing travel demand in the airport. Facilities that are unable to accommodate the increase in travel demand were identified for improvement. Thus, the improvement has to be done by expansion of terminal building, extending apron area for more aircraft parking spaces, additional runway length, increasing taxiways width as well as optimizing the operational processes by introducing flexibility and using technology.